Harms of cigarette smoking: call to increase knowledge among children. Issue 1 (January 2019) - Lonergan, Bradley; Harding, Victoria; Cohen, Hannah; Wylleman, Elisa; Cohen, Richard; Stebbing, Justin
Abstract : Although the major burden of disease caused by smoking is observed in the adult population, two-third of smokers start before the age of 18 years. Reducing the number of young smokers could lead to marked improvements to the health of the UK population and save billions of pounds in National Health Service finances. However, very little is known about what makes children decide to not smoke or to quit early. We believe that increased awareness of the health risks associated with smoking will reduce smoking uptake among children. This study identifies a significant lack of knowledge among children aged 11–17 years at two London secondary schools and potentially identifies an area for improving our antismoking programmes. Although 80% of pupils cited lung cancer as being a smoking-related disease, very few other conditions could be recalled. We must do all we can to reduce smoking uptake in children. Understanding their baseline knowledge is the first step towards addressing the deficits in our current antismoking programmes.